Ideology in Marine Ritual Discourse of Acehnese Speech Community - Pratiwy, Devi; Swastiwi, Anastasia Wiwik; Manugeren, M.; Pardi, Pardi; Asnani, Asnani (Jurnal Arbitrer, 2023)
This study is about what particular people belong to the particular ethnic have in mind as their ideology to see the environment, reflected from traditional fishing ritual in Acehnese speech community under the eco-linguistic perspective. In addition, with reference to social praxis, ecolinguistics recognizes three dimensions, namely ideological, sociological, and biological dimensions relating to the exploitation of the environment for fishing through ritual speech. The purpose of this study is to determine the ideology reflected in the speech. The study employed a qualitative research methodology, utilizing a phenomenological approach. The study makes use of verbal expressions expressed by naval commanders, gathered through a combination of participatory observation and comprehensive interviews at a central location of fish market and sanctuary in Banda Aceh, Aceh Indonesia. The data collected serve as the basis for the analysis and interpretation of the research findings. The respected ideology was then compared to the concept of ecosophy. The results of the analysis show that the ritual holistically contains the ideology of environmental preservation. The efforts to assist the natural, social, and spiritual preservations, specifically in marine environments, are obviously detected in the discourse. The ideology offered is in accordance with the concept of ecosophy, which includes beneficial discourse. However, part of the utterances also reflect the ambivalent discourse, but not the destructive one.